2021
DOI: 10.13075/mp.5893.01115
|View full text |Cite
|
Sign up to set email alerts
|

What is job crafting? Review of theoretical models of job crafting

Abstract: W ostatnich latach w psychologii pracy można zaobserwować wyraźny wzrost zainteresowania zjawiskami pozytywnymi. Jednym z nich są zachowania inicjowane przez pracowników, zmierzające do przekształcania warunków pracy w celu zwiększenia satysfakcji z pracy oraz jej dopasowania do potrzeb i zdolności. Zachowania te są nazywane kształtowaniem pracy (job crafting). Wraz rozwojem badań nad tym zagadnieniem powstawały, a następnie ewoluowały, jego odmienne koncepcje teoretyczne i definicje. Celem niniejszej pracy by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 41 publications
0
5
0
Order By: Relevance
“…It can be concluded that the perception of work by employees is strongly influenced by the competences of superiors and the span of their management. Other researchers [62], also by conducting meta-analyses [21], argue that job crafting brings many beneficial effects to employees and organizations. Those beneficial effects include an increase in commitment to work [5], strengthening of human resources [21]and improving employee wellbeing [6].…”
Section: Discussionmentioning
confidence: 99%
“…It can be concluded that the perception of work by employees is strongly influenced by the competences of superiors and the span of their management. Other researchers [62], also by conducting meta-analyses [21], argue that job crafting brings many beneficial effects to employees and organizations. Those beneficial effects include an increase in commitment to work [5], strengthening of human resources [21]and improving employee wellbeing [6].…”
Section: Discussionmentioning
confidence: 99%
“…In current study, we followed the role-based job crafting approach according to which three dimensions were framed for defining job crafting: task crafting, cognitive crafting and relational crafting (Kapica & Baka, 2021;Rudolph et al, 2017). The first dimension involves making changes in the number, types and scope at work to enhance assimilation into their own working lives, desire to create a positive self-image in their workplace and aspiration to get benefit from interpersonal relationships, all of which can be realized by job crafting.…”
Section: Backg Rou N Dmentioning
confidence: 99%
“…In current study, we followed the role‐based job crafting approach according to which three dimensions were framed for defining job crafting: task crafting, cognitive crafting and relational crafting (Kapica & Baka, 2021 ; Rudolph et al, 2017 ). The first dimension involves making changes in the number, types and scope at work by employees.…”
Section: Introductionmentioning
confidence: 99%
“…Team job crafting refers to the decision of team members to change their work content and approach through close collaboration and communication [34,35]. First, the boundaryspanning activities of collaborative innovation teams considerably impact the crafting of teamwork.…”
Section: Mediating Role Of Team Job Craftingmentioning
confidence: 99%
“…Leana and Cuguero-Escofet believe that in a work situation with a high task interdependence, members are more willing to participate in a cooperative negotiation process to change traditional work practices and solve problems more efficiently. Meanwhile, scout activities can make team members feel the pressure resulting from the competitive climate, creating a solid atmosphere of teamwork and improving the willingness of team members to make collective decisions and work together to achieve the same goal [34][35][36].…”
Section: Mediating Role Of Team Job Craftingmentioning
confidence: 99%